The Application of the Quality Management System of ISO 9001 - Syarifuddin T; Mahlia Muis; Andi Reni (Hasanuddin Journal of Business Strategy, 2021)
The research objective was to examine the application of the quality management system ISO 9001, and its supporting and inhibiting factors to leverage the employee performance at PT Tirta Sukses Perkasa. The paper applied a qualitative method using a phenomenological approach. Data obtained using observation and interviews from 3 informants. On the basis of the findings, the study found that the implementation of the 9001 quality management system to leverage employee performance refers to ISO 9001: 2008. The implementation follows several steps comprising of making company commitments, making company quality goals, forming an ISO team, making GAB assessment, making company policies, conducting ISO training, document preparation, quality management system implementation, internal quality audit training, management review, and external certification audit from ISO 9001 certification agency. The study found that the supporting factors for implementing the ISO 9001 management system are management commitment, facilities and infrastructure, effective communication, and availability of funds. Interestingly, there were several inhibiting factors that were work culture, understanding of the concept of the ISO 9001: 2008 Quality Management System, and time constraints.